Active Immunization Against Inhibin Impaired Spermatogenesis, Plasma Luteinizing Hormone, Pituitary Prolactin mRNA, and Hypothalamic Vasoactive Intestinal Peptide mRNA Expressions in Yangzhou Ganders - Muhammad Faheem Akhtar; Muhammad Umar; Ejaz Ahmad; Mingxia Zhu; Ying Han; Changfa Wang (Veterinary Sciences)
Inhibin (INH) plays a key role in the regulation of the reproductive performance of geese. It inhibits follicle-stimulating hormone (FSH) secretion from the anterior pituitary gland to regulate spermatogenesis. Immunization against INH in male geese leads to the production of antibodies to neutralize the INH activity that enhances testicular function and gonadotropin production. The objectives of the present research were to elaborate on the effects of inhibin (INH) immunization on testicular histology, plasma LH, pituitary PRL mRNA, and hypothalamic VIP mRNA expressions in Yangzhou ganders. A total of 60 birds were selected and divided into control (CON) and INH-immunized (INH-immunized) groups, having 30 in each group. In this experiment, the ganders were immunized with INH three times, and birds in the CON group were inoculated with bovine serum albumin (BSA). The analyzed data revealed that immunization against inhibin had no significant effects on improving the plasma concentration of LH hormone; however, significant effects were observed on the germ cell line, hypothalamic VIP mRNA, and pituitary PRL mRNA expressions. It is concluded that INH (INH) immunization is an effective tool to improve reproductive efficiency in Yangzhou ganders; however, INH immunization may harm pituitary PRL mRNA and hypothalamic mRNA expressions and LH plasma concentration. Seasonality played a vital impact on the hypothalamus–pituitary–gonadal (HPG) axis.